"IN THE CENTRE OF OUR CIRCLE": gender, selfhood and non-linear time in yvonne vera's nehanda. Issue 3 (4th July 2022) - Boulanger, Dorothée
Abstract: This article examines how non-linear time and circularity are deployed in the historical novel Nehanda (1993), written by Zimbabwean author Yvonne Vera. Using Adriana Cavarero's work on inclination, I suggest that circular time as well as spatial roundness, which pervade the novel, are mobilised to centre African women's voices, bodies and experiences of colonial domination and anticolonial struggles. Rehabilitating women as key historical agents of anticolonial mobilisation, Vera also proceeds to re-legitimise African knowledge production and transmission by highlighting the importance of orality, prophecy and spirituality in the fight against colonialism. Through its implicit critique of verticality, Nehanda calls into question both Western historiography on Africa and African patriarchal narratives of resistance and liberation. In a colonial context where verticality, inspired by Kant's philosophy, gestured towards the superiority of the European man as an autonomous subject, raising himself above the others, Vera highlights how Nehanda's authority and legacy stemmed from her "relational subjectivity" (Cavarero), that is, from the strength of her connection with her people, her land and her ancestors.